“Interacción entre la proteína de resistencia de yuca RXAM2 y efectores de Xanthomonas phaseoli pv. manihotis” - Silva Fernández, Lesly Ximena (Universidad Antonio Nariño, 2022)
The Cassava bacterial blight is a disease caused by the bacterium Xanthomonas phaseoli pv. manihotis (Xpm) and has been reported in all regions of the world where cassava is cultivated. The most economical and effective strategy for the management of the disease is the use of resistant varieties, but there have been few studies aimed at understanding the molecular basis of the resistance of cassava to this pathogen. Recently it was identified that the NLR protein named RXM2 confers resistance to different strains of Xpm. However, the molecular mechanism used by this protein to recognize Xpm effectors is unknown. This project allowed the generation of the possible three-dimensional structure of RXAM2 and XopE1, XopE4, XopC2, XopAK and XopV effectors of Xpm, by homology modeling. The LRR domain was identified as the possible responsible for the recognition of the effectors, through rigid and flexible molecular docking. On the other hand, it was possible to identify sites under negative selection in 65 Xpm strains, which suggests a high conservation between the effectors present in strains from different biogeographic regions.